OP0245-PARE Helping Patients to Make Informed Decisions. The Pare Guide to Disseminate Eular Recommendations Among Patients. (9th June 2015) - De Wit, M.; Bakker, M.; van Bodegom-Vos, L.; Buch, M.; Caeyers, N.; Carluccio, A.; Geenen, R.; Greiff, R.; Glüsing, B.; Gossec, L.; Kent, A.; Poldema, I.; et al.
Abstract : Background: Accurate patient information is necessary to make informed health decisions. However, the traditional, scientific wording of professional recommendations is often difficult to understand for lay people. Objectives: To develop a practical guide for patient organizations and health professionals to promote the dissemination of EULAR recommendations among patients. Methods: We conducted a Systematic Literature Review (SLR) of effective and feasible dissemination strategies to inform and educate patients about recommendations or guidelines. Two task force meetings took place to discuss the outcomes of the SLR and to develop a set of "points to consider" (i.e., advice based on literature and expert opinion) when developing and disseminating recommendations among patients. The task force comprised 7 patient representatives, 3 rheumatologists, 3 health professionals and 1 implementation specialist from 8 European countries. Results: The SLR showed that high quality studies on the effectiveness of dissemination strategies as well as the barriers for implementing a strategic dissemination approach are scarce. Out of 3143 unique publications only 12 studies could be included for review. These showed that a dissemination plan, written at the start of the recommendation development process, involvement of patients in this development process and the use of a combination of traditional and innovative dissemination tools, are key facilitators for success. These SLR findings have been used to write a practical guide for the development, translation, adaptation and dissemination of EULAR recommendations among patients and patient organisations. The booklet can be used by patient organisations and health professionals and contains suggestions, best practices and checklists to start the dissemination process. Conclusions: PARE produced a practical guide for disseminating recommendations among patients. In the coming year the guide will be used in a EULAR project about the dissemination of EULAR recommendations for glucocorticoid treatment in rheumatic diseases and a workshop at the PARE conference. Disclosure of Interest: None declared